Efectos en el rendimiento de la produccion de corcho al modificar el calibre de las planchas taponables (Scientia gerundensis, 1989)
The main purpose of this paper is to analise the posible effects of a diminution on the caliber of the bottle-cork on the economic profitability of the Extremadura cork-oak forest. A reduction from 22 mm to 17 mm in the wine-bottle neck will supose an increment of 27% in the raw production of bottle-cork.